Perencanaan Pengelolaan Tambang Pasir Besi di Kabupaten Kulon Progo dalam Perspektif Good Governance - Hidayat, Taufik; Pratiwi, Ratih Nur; Setyowati, Endah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This paper examines the relationship of good governance and management planning iron sand mine in Kulon Progo. Planning iron sand mining management in Kulon Progo views of the role of the main elements in the perspective of good governance, that the role of the private sector in this matter PT. JMI is more dominant. The role of PT. JMI management planning iron sand mine in Kulon Progo include: (a) general investigation such as engineering studies, economic studies and environmental studies (including social); (b) Exploration iron sand mine; (c) Construction mine;(d) mining; (e) processing, processing and refining; (f) Transportation; (g) Sales; and (h) reclamation. The government's role in planning the management of iron sand mining in Kulon Progo include: (a) permits; (b) Environmental Feasibility; and (c) Supervision. The role of the community in planning the management of iron sand mining in Kulon Progo very small only as a transmitter suggestions and opinions on the EIA.